Effect of Chlorpyrifos on Embryo Development of Wader Pari Fish (Rasbora lateristriata Bleeker, 1854) - Ascarti Adaninggar; Anita Restu Puji Raharjeng; Larasshita Putri Adhitya Sani; Jessy Octavia Harahap; Della Blatama; Sandi Francisco Pratama; Ardaning Nuriliani; Bambang Retnoaji; Hendry Tri Sakti SG Saragih (Fakultas Biologi Universitas Gadjah Mada, 2022)
Chlorpyrifos is an organophosphate insecticide, acaricide, and nematicide which is used to control leaf pests and soil pest insects. The insecticide chlorpyrifos works by disrupting the insect's nervous system. The use of insecticides on vegetable crops is generally more intensive than on other food crops so the negative impact on the biotic and abiotic environment becomes greater. The purpose of this study was to determine the negative impact of chlorpyrifos exposure with concentrations of 0.01, 0.1, 1 and 10 ppm on the embryonic development of Wader pari (Rasbora lateristriata). The results of observations at 24 and 48 hours showed that there were abnormalities in the development of the Wader pari’s embryo at the concentration of 0,1, 1 and 10 ppm, indicating that chlorpyrifos causes malformations in the form of defects in the development of the embryo of Wader pari fish.